Mapping of Sharia Cooperative Management Issue in Islamic Boarding Schools - Fatira AK, Marlya (Economica: Jurnal Ekonomi Islam, 2020)
Abstract:Â  This study aimed to identify and analyze the issue faced by Islamic boarding schools (Kepontren) in Medan. This research method is Participatory Learning and Action (PLA), data collection through interviews, direct observation, and documentation. The research location is in the city of Medan. The data in this study are primary. The results showed that the issue faced by the Kepontren in Medan City consisted of an internal issue and an external issue. Mapping the condition of the Medan City Islamic Boarding School Cooperatives shows that eight cooperatives. However, only three active participants (37.5%) are good enough and prosperous enough for their members; 62.5% are not developing, tend to be minor, and only sell the needs of the pesantren students. The implication of this research is to improve cooperative management in the pesantren environment in the city of Medan, especially in asset management, innovation, and strategy in human resource development. The novelty of this research is the application of Participatory Learning and Action from all environmental elements involved in the Pondok Pesantren cooperative.Abstrak: Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis permasalahan yang dihadapi oleh Pondok Pesantren (Kepontren) di Medan. Metode penelitian ini adalah Participatory Learning and Action (PLA), pengumpulan data melalui wawancara, observasi langsung, dan dokumentasi. Lokasi penelitian berada di kota Medan. Data dalam penelitian ini bersifat primer. Hasil penelitian menunjukkan bahwa permasalahan yang dihadapi oleh Kepontren di Kota Medan terdiri dari permasalahan internal dan permasalahan eksternal. Pemetaan kondisi Koperasi Pondok Pesantren Kota Medan menunjukkan bahwa terdapat delapan koperasi. Namun, hanya tiga peserta aktif (37,5%) yang cukup baik dan cukup sejahtera bagi anggotanya; 62,5% tidak berkembang, cenderung kecil, dan hanya menjual kebutuhan santri pesantren. Implikasi dari penelitian ini adalah untuk meningkatkan manajemen koperasi di lingkungan pesantren di kota Medan khususnya dalam pengelolaan aset, inovasi, dan strategi dalam pengembangan sumber daya manusia. Kebaruan dari penelitian ini adalah penerapan Participatory Learning and Action dari seluruh elemen lingkungan yang terlibat dalam koperasi Pondok Pesantren.